Conservation of moisture in the soil - Coe, William Arthur (My University, 1896)
Introduction: Conservation of moisture is a subject that is attracting considerable attention of late in these Western states. Some enterprising farmers are learning that the moisture in the soil can be controlled to a large extent. This was unknown throughout all the ages past up to within the last few years. The farmers in preparing their fields gave careful attention to a great many important matters such as fertilizing, crop rotation, fallowing, etc., but had never done anything about controlling the moisture already in the soil, except to drain off surplus water. When a drought came upon them and began withering their crops they were ignorant of what they should do. Some in the fear that want and starvation would confront them ire another harvest, have congregated and prayed for rain, all unmindful of the fact that tons upon tons of the so much coveted moisture was pouring forth from their fields moisture which to a great extent could be retained by proper cultivation.
Citation: Coe, William Arthur. Conservation of moisture in the soil. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Conservation; Moisture; Farmers; Fertilization; Theses; Manuscripts (documents)